The influence of ANC cadre empowerment on ANC visits of pregnant women in Bengkulu City - Yuniarti, Yuniarti; Yorita, Epti; Widiyanti, Desi; Destariyani, Elvi (Alma Ata University Press, 2024)
Background: Services during pregnancy are pregnancy health check-up services carried out by health workers, especially midwives or doctors for pregnant women which are carried out at least four times in pregnancy with details, namely one time gestational age 0-12 weeks, one time ANC gestational age 13-27 weeks and twice when the gestational age is 28-36 weeks. Based on the profile of K1 and K4 visits from 20 Public Health Centers in Bengkulu City, there are 3 Public Health Centers with K1 and K4 visits which are still low and have not reached the set targets and there is still a drop out where there is a decrease between K1 and K4 visits.Objectives: The study aims to knowing the influence of the empowerment of ANC the community health worker on the visit of ANC Pregnant Women in Bengkulu City Methods: This research uses a quasi-experimental method. The samples taken for the study were all pregnant women in Bengkulu City who were selected by purposive sampling. The sample consisted of 2 groups, namely the experimental group on pregnant women with the empowerment of ANC the community health worker and the ontrol group with counseling totaling 40 people. Data collection is carried out through data collection sheets and analyzed data with univariate and bivariate Data analysis used bivariate Results: The results of the study found that there was an Effect of Empowerment of ANC the community health worker on ANC visits to pregnant women in Bengkulu City in 2020Conclusions: The results Thisstudy was used as an alternative recommendation for increasing ANC visits